Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
[tex]d = \sqrt{(x_2 - x_1)^{2} + (y_2 - y_1)^{2}} \\d = \sqrt{(5 - 0)^{2} + (12 - 6)^{2}} \\d = \sqrt{(5)^{2} + (6)^{2}} \\d = \sqrt{25 + 36} \\d = \sqrt{61} \\d = 7.8 \\\\(x - h)^{2} + (y - k)^{2} = r^{2} \\(x - 5)^{2} + (y - 6)^{2} = 7.8^{2} \\(x - 5)^{2} + (y - 6)^{2} = 61 \\(h, k) = (5, 6)[/tex]
We can plug the two points into the distance formula.
[tex]\sf~d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
(0, 6), (5, 12)
x1 y1 x2 y2
Plug in what we know:
[tex]\sf~d=\sqrt{(5-0)^2+(12-6)^2}[/tex]
Subtract:
[tex]\sf~d=\sqrt{(5)^2+(6)^2}[/tex]
Simplify the exponents:
[tex]\sf~d=\sqrt{25+36}[/tex]
Add:
[tex]\sf~d=\sqrt{61}[/tex]
Simplify the square root:
[tex]\sf~d\approx\boxed{\sf7.81}[/tex]
[tex]\sf~d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
(0, 6), (5, 12)
x1 y1 x2 y2
Plug in what we know:
[tex]\sf~d=\sqrt{(5-0)^2+(12-6)^2}[/tex]
Subtract:
[tex]\sf~d=\sqrt{(5)^2+(6)^2}[/tex]
Simplify the exponents:
[tex]\sf~d=\sqrt{25+36}[/tex]
Add:
[tex]\sf~d=\sqrt{61}[/tex]
Simplify the square root:
[tex]\sf~d\approx\boxed{\sf7.81}[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.